A modified LI-RADS: targetoid tumors with enhancing capsule can be diagnosed as HCC instead of LR-M lesions - Min, Ji Hye; Kim, Jong Man; Kim, Young Kon; Kim, Honsoul; Choi, Gyu Seong; Kang, Tae Wook; Cha, Dongik; Hwang, Jeong Ah; Ko, Seong Eun; Ahn, Soohyun (European Radiology, 2022)
Objective: To elucidate whether the presence of enhancing capsule can be applied to establish a modified Liver Imaging Reporting and Data System (LI-RADS) to differentiate hepatocellular carcinoma (HCC) from non-HCC malignancies in extracellular contrast agent (ECA)–enhanced and hepatobiliary agent (HBA)–enhanced MRI. Methods: We enrolled 198 participants (161 men; mean age, 56.3 years) with chronic liver disease who underwent ECA-MRI and HBA-MRI before surgery for de novo hepatic nodule(s). Two reviewers assigned LI-RADS categories (v2018). We defined a “modified LR-5 category, which emphasizes enhancing capsule (mLR-5C)” over targetoid features and classifies tumors with both targetoid appearance and enhancing capsule as HCC instead of LR-M. We compared the diagnostic performance of conventional LI-RADS and modified LI-RADS criteria for both MRIs. Results: A total of 258 hepatic nodules (194 HCCs, 43 benign lesions, and 21 non-HCC malignancies; median size, 19 mm) were analyzed. By conventional LI-RADS, 47 (18.2%) nodules (31 HCCs and 16 non-HCC malignancies) were categorized as LR-M. The mLR-5C criterion showed superior sensitivity (ECA-MRI, 76.6% vs. 67.0%; HBA-MRI, 60.4% vs. 56.3%; both p < 0.05) while maintaining high specificity (ECA-MRI, 93.8% vs. 98.4%; HBA-MRI, 95.3% vs. 98.4%; both p > 0.05) compared with the LR-5 criterion. Using the mLR-5C criterion, ECA-MRI exhibited higher sensitivity than HBA-MRI (76.6% vs. 60.4%, p < 0.001) and similar specificity (93.8% vs. 95.3%, p > 0.99). Conclusion: Our modified LI-RADS achieved superior sensitivity for diagnosing HCC, without compromising specificity compared with LR-5. ECA-MRI showed higher sensitivity in diagnosing HCC than HBA-MRI by applying the mLR-5C for LR-M lesions. Key Points: • By conventional LI-RADS, 31 (16.0%) of 194 HCCs were categorized as LR-M. • Among 31 HCCs categorized as LR-M, 19 HCCs or 8 HCCs were recategorized as HCC on ECA-MRI or HBA-MRI, respectively, after applying the modified LR-5 category, which allocates targetoid lesions with enhancing capsule as mLR-5C instead of LR-M. • The mLR-5C showed superior sensitivity compared with the LR-5 in both MRIs (ECA-MRI, 76.6% vs. 67.0%; HBA-MRI, 60.4% vs. 56.3%, both p < 0.05), while maintaining high specificity (ECA-MRI, 93.8% vs. 98.4%; HBA-MRI, 95.3% vs. 98.4%; both p > 0.05).
Keywords: Carcinoma, Hepatocellular; Contrast Media; Humans; Liver Neoplasms; Magnetic Resonance Imaging; Male; Middle Aged; Retrospective Studies; Sensitivity and Specificity; Carcinoma, hepatocellular; Liver Imaging Reporting and Data System; Magnetic resonance imaging